Corpus-based Critical Discourse Analysis on AI Policy: A Comparison Between North America and Developing Countries in East Asia (Asian Journal of Social Science Studies, 2023)
Artificial Intelligence (AI) has undergone a global transformative impact on people‘s lives. However, the realm of empirical research focused on AI within applied linguistics remains limited, predominantly dwelling on qualitative rhetoric and narrative analysis. This research aims to fill this gap by shedding light on the discursive constructions of AI policies between North America and developing countries in East Asia based on corpus data. Two corpora are constructed for quantitative study, utilizing keywords, collocates, and concordance analysis, and two dimensions of dialectical-relational approach are adopted to delve into the results. The findings reveals that both EA and NA prioritize AI-related efforts, but EA emphasizes more on economic and societal applications, while NA highlights governmental sectors‘ efforts, cooperation with allies, and national security in AI deployment. The results are closely associated with their social context. This nuanced understanding of AI policy research holds significant implications for policymakers, stakeholders, and scholars actively involved in shaping responsible AI regulations and governance practices on an international scale.